SOSIALISASI GERAKAN CERDAS PENGELOLAAN SAMPAH PADA SISWA SDN 3 KLALING KUDUS - Siti Amaroh; Maura Emisha Bilvi Ajna; Faradilla Choirun Nisa; Nurul Kholifatur Rosidah; Nurul Karina (LPPM STAI Muhammadiyah Probolinggo, 2026)
Waste management remains a significant environmental challenge in Indonesia, including in school environments that often lack proper waste management systems. Low student awareness in disposing of and sorting waste can negatively affect school cleanliness and the development of environmentally responsible behavior. This community service activity aims to improve elementary school students’ knowledge and awareness of waste management through a smart waste management socialization program. The activity was conducted at SDN 3 Klaling Kudus and involved fourth-grade students as participants. The implementation method consisted of three stages: preparation, implementation, and evaluation. During the implementation stage, activities included the delivery of educational materials on types and impacts of waste, interactive games on waste sorting, and hands-on practice in separating organic and inorganic waste. Evaluation was carried out through observation, question-and-answer sessions, and simple quizzes to measure students’ understanding. The results indicate an improvement in students’ knowledge, participation, and awareness in maintaining cleanliness and sorting waste properly. This activity effectively promotes environmentally responsible behavior among elementary school students.